Textural, Flow and Viscoelastic Properties of Hass Avocado (Persea Americana Mill.) During Ripening Under Refrigeration Conditions - Osorio-Lira, F (Elsevier Ltd, 2018)
Microstructural and rheological changes in whole and ground (purée) mesocarp of Hass avocado (Persea americana Mill.) were studied under storage conditions (40 days at 10 °C). The maximum stress (σmax), relaxation test and microstructural changes were applied to mesocarp chunks. The shear stress (τ), apparent viscosity (η) and complex modulus of viscoelasticity (G*) were analyzed in the mesocarp purée. The ripening produced a decrease in σmax in both harvest, observing microstructural damage of the plant tissue over 30 days. The values of τ and η decreased, adjusting well to the Cross - Willianson (R2 = 0.95–0.94) and Herschel - Bulkley (r2 = 0.91–0.98) models. G* has an elastic tendency (G′) with a decrease in hysteresis. The results corroborate the impact of ripening on the rheological properties of the fruit. © 2017 Elsevier Ltd